Cellular automata model: an application to landslide dam of “le mottacce” (tuscany, central italy) - Cencetti, Corrado; De Rosa, Pierluigi; Fredduzzi, Andrea (Italian journal of engineering geology and environment, 2011)
<span data-sheets-value="{"1":2,"2":"This study analyzes the phenomenon of landslide dams by means of a quantitative approach, that consists in the implementation of a specific cellular automata model: CAESAR (COULTHARD et alii, 2002) a 2D model developed to simulate the morphological trend of a river within its hydrographic basin, including the calculation of the flow depth and a more detailed representation of sediment transport using multiple grain sizes. A code modification of CAESAR (DE ROSA, 2008) has been introduced to simulate a large amount of sediments coming into the river from the slopes (i.e. landslide dams).\rIn this paper we present the first application of the modified CAESAR on a real case: the landslide occurred on 27th November 1987 in “Le Mottacce” (Upper Basin of Arno River). The landslide, which had a front of about 100 m, cut off both the Arezzo-Stia railways and the close provincial road and occluded the river-bed for 2/3 of its width.\rThe comparison between the real landslide and the performed simulation demonstrates that the CAESAR modified model can correctly simulate the real case: the landslide, simulated by the model, produces the partial blockage (about 2/3) of the river bed, and the landslide body moves in the same way that occurred in reality."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">This study analyzes the phenomenon of landslide dams by means of a quantitative approach, that consists in the implementation of a specific cellular automata model: CAESAR (COULTHARD et alii, 2002) a 2D model developed to simulate the morphological trend of a river within its hydrographic basin, including the calculation of the flow depth and a more detailed representation of sediment transport using multiple grain sizes. A code modification of CAESAR (DE ROSA, 2008) has been introduced to simulate a large amount of sediments coming into the river from the slopes (i.e. landslide dams). In this paper we present the first application of the modified CAESAR on a real case: the landslide occurred on 27th November 1987 in “Le Mottacce” (Upper Basin of Arno River). The landslide, which had a front of about 100 m, cut off both the Arezzo-Stia railways and the close provincial road and occluded the river-bed for 2/3 of its width. The comparison between the real landslide and the performed simulation demonstrates that the CAESAR modified model can correctly simulate the real case: the landslide, simulated by the model, produces the partial blockage (about 2/3) of the river bed, and the landslide body moves in the same way that occurred in reality.